Effect of Provocative Test in Hypermetropic Eyes: A Comparative Study - Uzma Fasih, Erum Shahid, Arshad Shaikh, Muzna Kamal, Asad Raza Jaffery (Pakistan Journal of Ophthalmology, 2016)
Purpose: To determine the effect of Mydriatic provocative test on intraocular pressure in hypermetropic eyes as compared to emmetropic eyes. Study Design: Prospective analytic cohort study. Place and Duration: Department of ophthalmology, Abbasi Shaheed Hospital, Karachi between October 2014 to July 2015. Material and Methods: We recruited 109 patients from eye OPD who were emmetropic, hypermetropic and presbyopic. We excluded known cases of glaucoma, closed angle, operated cases and using topical medications. After taking detail history and examination, IOP was measured then tropicamide was instilled. After mydriasis IOP was again measured. Data was collected and analyzed on SPSS 21. A descriptive analysis of continues and categorical variables was performed. Means of IOP was compared before and after dilatation in hypermetropes and emmetropes. Results: We had 109 eyes of 109 patients in which 27 (25%) were males and 82 (75%) were females. Their mean age was 44.2 ± 8.81SD. Emmetropic eyes were 58 (53%) and hypermetropic eyes were 51 (47%).Mean base line IOP before dilatation was 14.7 ± 2.2SD and after dilatation was15.4 ± 2.8.The means of IOP before and after dilatation was compared in hypermetropes with emmetropes with help of Independent t test. Its value is 0.322. Conclusion: There was no statistically significant difference in intraocular pressure after mydriasis in hypermetropes as compared to emmetropes. Provocative test was not positive in any group so we accept null hypothesis. Key Words: Provocative test, hypermetropes, mydriasis, intraocular pressure